2010
DOI: 10.1016/j.autrev.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

PD-1, gender, and autoimmunity

Abstract: Programmed death 1 (PD-1) and its ligands (PD-L1 and PD-L2) are responsible for inhibitory T cell signaling that helps mediate the mechanisms of tolerance and immune homeostasis. The PD-1:PD-L signaling pathway has been shown to play an important role in a variety of diseases, including autoimmune conditions, chronic infection, and cancer. Recently, investigators have explored the role of sex hormones in modulating the pathway in autoimmune conditions. Exploring the effects of sex hormones on the PD-1:PD-L pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 90 publications
1
47
0
2
Order By: Relevance
“…Female gender was associated with increased PDCD1LG2 expression in a study of hematopoietic neoplasms (44), similar to our findings in colorectal carcinoma. Sex hormones, such as estrogens, may upregulate cellular expression of immune checkpoint molecules, including the PDCD1 and its ligand CD274, in a variety of cell types (45,46). Taken together, our population-based data will likely inform further mechanistic studies to clarify potential roles of female sex hormones in the regulation of the immune checkpoint pathway in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Female gender was associated with increased PDCD1LG2 expression in a study of hematopoietic neoplasms (44), similar to our findings in colorectal carcinoma. Sex hormones, such as estrogens, may upregulate cellular expression of immune checkpoint molecules, including the PDCD1 and its ligand CD274, in a variety of cell types (45,46). Taken together, our population-based data will likely inform further mechanistic studies to clarify potential roles of female sex hormones in the regulation of the immune checkpoint pathway in the tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Programmed cell death 1 (PD-1) and its ligands, Programmed death ligands 1 and 2 (PD-L1 and PD-L2), have important regulatory functions (Dinesh et al, 2010). Accumulating evidence points to a crucial role for the PD-1 pathway in peripheral tolerance.…”
Section: Expression Of Pd-1 (Cd279) On Cd4 and Cd8 T Cellsmentioning
confidence: 99%
“…PD-1 and PD-L interactions are important in the control of both the initial phase of activation and expansion of self-reactive T cells as well as of the effector functions of self-reactive T cells and injury to target organs (Keir et al, 2006(Keir et al, , 2007. PD-1-deficient mice develop spontaneous autoimmune diseases, indicating an essential function of PD-1 in the mechanisms of tolerance (Dinesh et al, 2010;Nishimura et al, 1998Nishimura et al, , 1999Nishimura et al, , 2001 While CTLA-4 expression is restricted to T cells, PD-1 is expressed on T and B cells, natural killer T cells and monocytes (Kristjansdottir et al, 2010), thus indicating a broader role for PD-1 in immune regulation. Probst et al (2005) suggested that CTLA-4 and PD-1 act synergistically and demonstrated that these are crucial molecules for peripheral CD8 T cell tolerance induced by resting dendritic cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, SLE shows a prevalence that is nine times as great in the former, and in other autoimmune diseases like Sjörgen's syndrome and rheumatoid arthritis, the proportions are 9:1 and 2-7:1 respectively [1,107]. Some authors consider this a phenomenon of "female-biased autoimmunity", but they recognize that the role of sex hormones, particularly estrogens, should be re-evaluated with more modern research tools [108][109][110]. Recent research suggests that the hormone mediated effects on the protein called programmed cell death 1 (PD-1) signaling pathway can play an important role in modulating autoim unity [C].…”
Section: Sex Hormones and Systemic Lupus Erythematosusmentioning
confidence: 97%